Nickel alloys for electronics (Nickel Development Institute reference book series, 1987)
This reference book is intended to provide information that will be directly applicable to engineers and designers in evaluating and applying the nickel alloys that are most useful to the electronics industry. The materials included in this reference book are based on generic alloys that have industry specifications and Unified Numbering System (UNS) numbers. --